Bioinspired nanoerythrocytes for metabolic microenvironment remodeling and long-term prognosis promoting of acute ischemic stroke. (April 2023) - Liu, Peixin; Zhang, Tongyu; Li, Chao; Zhang, Yiwen; Zhou, Zheng; Zhao, Zhenhao; Chen, Qinjun; Sun, Tao; Jiang, Chen
Abstract: Metabolic microenvironment dysfunction remains hallmarks of acute ischemic stroke (AIS) throughout the ischemia, reperfusion, and recovery stages. Existing therapeutic strategies focus only on a single pathological process, while cascading metabolic changes are neglected. For the sake of better long-term prognosis, interventions in each stage are certainly worthwhile if achievable. Herein, inspired by the natural hemoglobin (Hb) carrying oxygen mechanism, a polymer-based nanoerythrocyte is designed to remodel the metabolic microenvironment in the whole stages of AIS. Briefly, Hb and methoxatin are incorporated into polydopamine nanocage which is further coated with the polymer layer formed by in-situ free radical polymerization. Modified with microthrombus-targeting peptide, this nanoerythrocyte can actively accumulate in the ischemic core and respond to the metabolic microenvironment. In vivo results demonstrate that cellular metabolic homeostasis and responsiveness are restored by oxygen balance regulation, microglia polarization, glucose metabolism activation, and neovascularization in permanent and transient middle cerebral artery occlusion model mice. The behavioral experiment results also confirm the effects of nanoerythrocyte for long-term prognosis. This strategy gives a proof of concept that metabolic microenvironment modulation is a promising perspective for AIS treatment with nanoerythrocytes. Graphical Abstract: Bioinspired nanoerythrocyte is developed to target microthrombus in ischemic core and modulate metabolic microenvironment in the whole stages of AIS. Multiple therapeutic effects are achieved by hypoxia relief in the ischemia stage, ROS inhibition and microglia polarization in the acute reperfusion stage, glucose metabolism activation and BBB repair in the recovery stage. Motor functions and long-term prognosis are restored in MCAO model mice after treatment. ga1 Highlights: Microthrombus-targeted nanoerythrocyte penetrates the damaged blood-brain barrier and reaches the ischemic core. Nanoerythrocyte responds to the level of oxygen and reactive oxygen species during different stages of acute ischemic stroke. A multi-cellular metabolic modulation strategy is beneficial for the long-term prognosis of acute ischemic stroke.